WARENESS ON DEPRESSION AMONG FIRST YEAR MEDICAL STUDENTS IN UDAYANA UNIVERSITY - Subramaniam, Vickram; Wahyuni, A A Sri (Bali Journal of Medical and Health Sciences, 2017)
The field of medical knowledge is immense and has different stages of training which a medical student must undergo in which studies show a high prevalence of psychological morbidity during these stages. Depression is one of the most common psychological morbidity in this demographic, with prevalence of depression up to 70% in several studies. Therefore, it is important to investigate the prevalence and risk factors of depression, especially in medical students. A descriptive cross sectional study was done on the first year medical student of the Faculty of Medicine of Udayana University from November 2015 to January 2016. The samples was selected using simple random sampling. Interview using questionnaire was done on students chosen as samples, and depression status was assessed using Beck,s Depression Inventory (BDI). Of 100 samples, 68% was categorized as normal, 26% as mild mood disturbances, 3% as borderline clinical depression, 2% as moderate depression, and 1% as severe depression. Depression was more common in younger students aged 16-17 years old, female, students who lives alone, those with introverted personality, students who prefer reading and being alone, and those reported decreased body weight and sleeping difficulty.   keyword:awareness, depression, medical student